Causal Model of Emotional Intelligence, Digital Literacy, and Employee Work Productivity of Banking Staff in Kupang: A Structural Equation Modeling Approach - Moni Y. Siahaan; Klaasvakumok J. Kamuri (CV. Vocezmi Learnov, 2025)
The ongoing transformation of the workplace, driven by the Industrial Revolution 4.0 and the paradigm of Society 5.0, has intensified the demand for human resources equipped with advanced emotional and digital capabilities. This study develops a comprehensive causal framework that examines the interrelationships among emotional intelligence, digital literacy, and employee productivity using a Structural Equation Modeling (SEM) approach. The empirical evidence demonstrates that emotional intelligence significantly enhances productivity by fostering stronger emotional regulation, adaptive responses to organizational change, and effective interpersonal collaboration. Digital literacy is likewise a crucial determinant of productivity, enabling employees to utilize digital technologies more efficiently to achieve performance targets. Furthermore, the results indicate that emotional intelligence positively contributes to the development of digital literacy, suggesting that emotionally competent individuals exhibit greater openness and motivation toward technological adaptation. Importantly, digital literacy acts as a significant mediating mechanism linking emotional intelligence to productivity, emphasizing the need for organizations to strategically cultivate both competencies in synergy. The study advances the theoretical discourse on employee productivity by conceptualizing the integrated roles of emotional and digital competencies and provides actionable insights for organizations to design holistic human resource development initiatives that align with the rapidly digitalized and dynamic characteristics of contemporary work environments.